2020
DOI: 10.3390/agronomy11010010
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Environmental Samples for PCR Detection of Phytopathogenic Bacteria: A Case Study of Citrus Huanglongbing Disease

Abstract: Huanglongbing (HLB) is the most devastating citrus disease and is associated with three bacterial species of the genus ‘Candidatus Liberibacter’ transmitted by insect vectors. The early detection of HLB is based on PCR methods, and it is one of the cornerstones for preventing incursion into disease-free countries. However, the detection of phytopathogenic bacteria with PCR-based methods is problematic in surveys that include a variety of samples of different origins. Here, we first report the proportion of amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Besides their intervention in Erwinia transmission, insects are also responsible for the dispersion of the aggressive citrus disease, Huanglongbing disease (citrus greening), caused by the Gram-negative “ Candidatus Liberibacter”; this genus is responsible for the phloem vessels infections [ 118 , 119 , 120 ]. The term “ Candidatus ” refers to the impossibility to cultivate and grow this bacteria group in laboratory conditions [ 118 ], which is also difficult to detect as it is only possible through molecular methods such as PCR-based techniques [ 120 , 121 ]. There are three major species of this group mainly dispersed in Asia, Africa [ 122 , 123 ], and America [ 124 , 125 ] that can be transmitted by different vectors.…”
Section: Phytopathogenic Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Besides their intervention in Erwinia transmission, insects are also responsible for the dispersion of the aggressive citrus disease, Huanglongbing disease (citrus greening), caused by the Gram-negative “ Candidatus Liberibacter”; this genus is responsible for the phloem vessels infections [ 118 , 119 , 120 ]. The term “ Candidatus ” refers to the impossibility to cultivate and grow this bacteria group in laboratory conditions [ 118 ], which is also difficult to detect as it is only possible through molecular methods such as PCR-based techniques [ 120 , 121 ]. There are three major species of this group mainly dispersed in Asia, Africa [ 122 , 123 ], and America [ 124 , 125 ] that can be transmitted by different vectors.…”
Section: Phytopathogenic Bacteriamentioning
confidence: 99%
“…There are three major species of this group mainly dispersed in Asia, Africa [ 122 , 123 ], and America [ 124 , 125 ] that can be transmitted by different vectors. In Europe, the dispersion of these species is also a concern since there are already reports of the presence of vectors in the Atlantic Coast of Portugal and northwest of Spain [ 118 , 126 , 127 ].…”
Section: Phytopathogenic Bacteriamentioning
confidence: 99%
“…All of them were positive by new protocol, with C q which ranged from 23.0 ± 2.9 to 33.2 ± 4.2 (data not shown). No amplification was detected in the 105 non-target plant and insect samples analyzed, including the strain BT-1 of L. crescens and those samples that gave undesired amplifications with other PCR protocols, as described in Morán et al 47 .…”
Section: Resultsmentioning
confidence: 99%
“…universal real-time PCR by Bertolini et al 46 has been removed as it produces false-positive results 36 . However, recent works have demonstrated that both real-time PCRs by Bertolini et al 46 and Li et al 44 , although with a good sensitivity, produced undesired amplifications in environmental samples due to their highly conserved nature of the 16S rRNA gene used as target 47 . Other universal real-time PCR protocols, such as Ananthakrishnan et al 48 , based on other genes, have been described but not validated according to EPPO requirements 49 .…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, the detection of plant pathogenic bacteria is made from samples of different environmental origin: soils and plant debris, living plants, and insects. Diagnosis of HLB using standardised RT-PCR methods was attempted from samples taken from plants, psyllid vectors, and parasitoids of the psyllid (Morán et al, 2021), a total of 4915 samples. A total of 2783 samples were taken from asymptomatic plants collected in surveys made between 2009 and 2018 in Spain.…”
Section: Candidatus Liberibacter Asiaticus and Vectors (*: See Also R...mentioning
confidence: 99%